2014
DOI: 10.1177/2167696814561767
|View full text |Cite
|
Sign up to set email alerts
|

Is Emerging Adults’ Attachment Preference for the Romantic Partner Transferred From Their Attachment Preferences for Their Mother, Father, and Friends?

Abstract: This study examined whether emerging adults' attachment preference for their romantic partner is complementary to their attachment preferences for their mother, father, and friends using a cross-sectional research design. Participants were 1,021 emerging adults recruited in the Czech Republic (mean age ¼ 21.46, SD ¼ 1.55) who filled out questionnaires. The attachment preference for the romantic partner correlated inversely with the attachment preference for friends but not with the preference for the mother or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 53 publications
6
29
0
1
Order By: Relevance
“…Research has indicated that romantic partners increase in importance within the attachment hierarchy towards later adolescence (Rosenthal & Kobak, 2010). Young people who had been in a dating relationship for at least two years reported that their partner met the four primary attachment characteristics, whereas for those who had not 7 ATTACHMENT HIERARCHIES FOR SPANISH ADOLESCENTS been in a dating relationship for this length of time, family members continued to fulfil some of these characteristics (Hazan & Zeifman, 1999;Hazan, Zeifman & Middleton, 1994;Fearon & Roisman, 2017;Umemura et al, 2014).…”
Section: Attachment Hierarchies For Spanish Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that romantic partners increase in importance within the attachment hierarchy towards later adolescence (Rosenthal & Kobak, 2010). Young people who had been in a dating relationship for at least two years reported that their partner met the four primary attachment characteristics, whereas for those who had not 7 ATTACHMENT HIERARCHIES FOR SPANISH ADOLESCENTS been in a dating relationship for this length of time, family members continued to fulfil some of these characteristics (Hazan & Zeifman, 1999;Hazan, Zeifman & Middleton, 1994;Fearon & Roisman, 2017;Umemura et al, 2014).…”
Section: Attachment Hierarchies For Spanish Adolescentsmentioning
confidence: 99%
“…ATTACHMENT HIERARCHIES FOR SPANISH ADOLESCENTS However, it has been suggested that peer attachments may not be as strong as attachments to others (Rosenthal & Kobak, 2010). The extant literature is mostly consistent in noting that parents, not peers, are typically retained as primary attachment figures through late adolescence and even early adulthood, especially among secure adolescents, or those who are not in longterm romantic relationships (Julal, Carnelley & Rowe, 2017;Pinquart, FeuBner & Ahnert, 2013;Umemura, Lacinová & Macek, 2014). Friends assume functions such as safety or proximity seeking, although this does not imply that all characteristics of attachment are transferred from the family context to the peer context; nor do friends become true attachment figures.…”
mentioning
confidence: 99%
“…According to his theory, there should be more attachment behavior directed toward attachment figures than nonattachment figures, as only attachment figures are the set-goals of the attachment behavioral system. The criterion of selectivity has been emphasized by other scholars (Rosenthal & Kobak, 2010;Umemura, Lacinová, & Macek, 2015;Weiss, 1991;Zeifman & Hazan, 2008). Bowlby's (1982) third criterion involves the increase in the person's attachment behavior toward the attachment figure when the attachment system is more highly activated.…”
Section: Bowlby's Attachment Figure Criteriamentioning
confidence: 97%
“…According to his theory, there should be more attachment behavior directed toward attachment figures than nonattachment figures, as only attachment figures are the set‐goals of the attachment behavioral system. The criterion of selectivity has been emphasized by other scholars (Rosenthal & Kobak, ; Umemura, Lacinová, & Macek, ; Weiss, ; Zeifman & Hazan, ).…”
Section: Two Sets Of Definitional Criteria For Attachment Figuresmentioning
confidence: 98%
“…The data and ethical approval for this study were drawn from the "Paths to adulthood" project, an ongoing longitudinal study that focuses on the psychosocial development of emerging adults in the Czech Republic (Macek et al, 2016;Umemura, Lacinová, & Macek, 2015). The major aims of this project are to explore the process of transition from adolescence to adulthood and to describe the individual psychological characteristics specific to this period.…”
Section: Procedures and Participantsmentioning
confidence: 99%